Comparison of Change in Periodontal Risk in Adult Patients Following Phase I Therapy – A Preliminary Study: Life Sciences-Periodontics&Dentistry - Shetty, Shreya; Fatani, Ola Hashim; Aljabri, Raghad Abdulhadi; Alameel, Nojoud Mohammed; Lardhi, Nour Abdulmajeed; Shaikh, MS Khammarunissa (International Journal of Life Science and Pharma Research, 2022)
Periodontal risk assessment is essential to ensure the successful outcome of periodontal therapy. Various assessment tools have been devised over the years of which the periodontal risk assessment(PRA) tool by Lang & Tonetti is one of the more authentic tools, and it assesses the risk of severity of periodontal disease by taking into account various components which are a combination of risk factors, indicators, and markers. The present study used this tool to evaluate the change in periodontal risk following phase 1 periodontal therapy. Following the approval from the institutional ethical committee, 299 male and female patients aged 18 to 60 years undergoing comprehensive clinical care (CCC) at ISNC dental clinics from October 2020 until April 2021 were selected, and PRA was assessed at baseline (before phase 1 therapy) and following a re-evaluation of phase 1 therapy (4-6 weeks after phase 1 therapy). All the parameters of the Lang and Tonetti’s PRA model were recorded, and the periodontal risk was calculated accordingly. The data collected was entered into a Microsoft excel sheet. Statistical analysis was carried out using SPSSV 22 software. The results showed significant differences in essential risk parameters – sites with bleeding on probing(BOP), alveolar bone loss, and polygon surface area for risk. (P<0.05). These were the expected parameters to change following phase -1 therapy, thus having a profound influence on the periodontal risk. However, chi-square values showed no changes in systemic and general factors and smoking. (P>0.05) These factors are usually permanent and often impossible to eliminate, even if under control. Concerning smoking, even if the patients quit or reduce the number of cigarettes smoked, the alteration in risk levels is minimal or negligible. Thus, Phase 1 periodontal therapy significantly influences the risk levels in adult patients.